The Comparison of Access Point Signal Gain with Beverage Cans - Ni Wayan Sri Ariyani (International Journal of Informatics and Communication Technology (IJ-ICT), 2015)
Computer network development depends on the development of information technology and communication. Several things as the reasons to develop the technology of computer network are implementing communication flexibly which in this case in the theory of computer network is to build wireless network communication. The existence of wireless communication as the comparison against wired network, having different impairment compared to wired communication. One of which is the weakening of wireless signal strength towards the ongoing communication distance. Therefore in wireless communication currently plenty of it being implemented, to handle the occurring impairment due to distance influence, it is needed for signal amplifier device. One of signal amplifier that can be used in the surroundings which is economical and practical is by using used beverage can.